La violence dans les maisons centrales de femmes de Cadillac et de Montpellier au XIXe siècle - Anna Le Pennec (Criminocorpus)
Symptomatic mark of virility in a virility world, jail violence is automatically associated to a male practice. However, 19th century’s prison archives treating of non-mixed jails in the South West of France mention numerous cases of physical and verbal abuses among women. Based on institutional violence, staff and prisoners inflict and experience abuses. Some of them combine both by attempting suicide. The nature of the gesture or speech, the reasons that caused it and the moral judgment associated to it, can vary considerably. The article will be discussing the interactions and mechanisms underlying these violence and speeches.